Urinary p75ECD: A prognostic, disease progression, and pharmacodynamic biomarker in ALS. (21st March 2017) - Shepheard, Stephanie R.; Wuu, Joanne; Cardoso, Michell; Wiklendt, Luke; Dinning, Phil G.; Chataway, Tim; Schultz, David; Benatar, Michael; Rogers, Mary-Louise
Abstract : Objective: To evaluate urinary neurotrophin receptor p75 extracellular domain (p75 ECD ) levels as disease progression and prognostic biomarkers in amyotrophic lateral sclerosis (ALS). Methods: The population in this study comprised 45 healthy controls and 54 people with ALS, 31 of whom were sampled longitudinally. Urinary p75 ECD was measured using an enzyme-linked immunoassay and validation included intra-assay and inter-assay coefficients of variation, effect of circadian rhythm, and stability over time at room temperature, 4°C, and repeated freeze-thaw cycles. Longitudinal changes in urinary p75 ECD were examined by mixed model analysis, and the prognostic value of baseline p75 ECD was explored by survival analysis. Results: Confirming our previous findings, p75 ECD was higher in patients with ALS (5.6 ± 2.2 ng/mg creatinine) compared to controls (3.6 ± 1.4 ng/mg creatinine, p < 0.0001). Assay reproducibility was high, with p75 ECD showing stability across repeated freeze-thaw cycles, at room temperature and 4°C for 2 days, and no diurnal variation. Urinary p75 ECD correlated with the revised ALS Functional Rating Scale at first evaluation ( r = −0.44, p = 0.008) and across all study visits ( r = −0.36, p < 0.0001). p75 ECD also increased as disease progressed at an average rate of 0.19 ng/mg creatinine per month ( p < 0.0001). In multivariate prognostic analysis, bulbar onset (hazard ratio [HR] 3.0, p = 0.0035), rate of disease progression from onset to baseline (HR 4.4, p < 0.0001), and baseline p75 ECD (HR 1.3, p = 0.0004) were predictors of survival. Conclusions: The assay for urinary p75 ECD is analytically robust and shows promise as an ALS biomarker with prognostic, disease progression, and potential pharmacodynamic application. Baseline urinary p75 ECD provides prognostic information and is currently the only biological fluid–based biomarker of disease progression.